Utilization of Digital Elevation Models in Slope Morphology Analysis for Landslide Identification in Ternate City, Indonesia - Rakuasa, Heinrich; Budnikov, Viktor Vladimirovich; Adifan, Muhammad Rayhan (MSD Institute, 2024)
Ternate City, located in the North Maluku archipelago, Indonesia, has hilly geographical and morphological conditions that make it vulnerable to landslides. This research aims to identify potential landslide risks by utilizing the Digital Elevation Model and slope morphology analysis and provide recommendations for disaster mitigation. This study used Digital Elevation Model (DEM) data obtained from the Indonesian Geospatial Information Agency, as well as land use data extracted from Sentinel 2 satellite imagery. The Slope Morphology (SMORPH) method was applied to analyze the shape and slope, which was then used to generate a landslide potential map. The analysis results show that 1,391.72 hectares of area in Ternate City have a high risk of landslides, with factors such as slope, slope shape, and land use conditions contributing to soil stability. The study also identified the importance of risk mapping and socialization to the community on early signs of landslides to improve preparedness. This research confirms the need for comprehensive and sustainable mitigation efforts to reduce the impact of landslides in Ternate City. Recommendations include infrastructure strengthening, drainage channel construction, and reforestation in critical areas. The results of this study are expected to serve as a basis for policymakers to formulate more effective disaster mitigation strategies and increase public awareness of the importance of wise environmental management.